Assessment of Cardiovascular Risk Factors in Adult General Out-patient Clinics in Nigeria: A Country Analysis of The Africa and Middle East Cardiovascular Epidemiological (ACE) Study - Geoffrey C. Onyemelukwe; Oluwagbenga Ogunfowokan; Amam Mbakwem; A. Kayode Alao; Kodjo Soroh; Osahon Omorodion; Paula Abreu (Challenges in Disease and Health Research Vol. 5, 2021)
Background: With globalization and rapid urbanization, demographic and epidemiologic transitions have become important determinants for the emergence of cardiovascular disease (CVD). Cardiovascular disease (CVD) has emerged in recent decades as a major cause of morbidity and mortality worldwide An estimated 17-million deaths globally were due to CVD in 2002, and CVD or stroke are projected to become the worldwide leading cause of morbidity and mortality by 2020. Objective: To estimate the prevalence of CVD risk factors in adult out-patients attending general practice and non-specialist clinics in urban and rural Nigeria. Methods: As part of the Africa and Middle East Cardiovascular Epidemiological (ACE) study, a cross-sectional epidemiologic study was undertaken for the presence of hypertension, diabetes mellitus, dyslipidemia, obesity, smoking and abdominal obesity in Nigeria. Results: In total, 303 subjects from 8 out-patient general practice clinics were studied, 184 (60.7%) were female and 119 (39.3%) were male. Mean age was 42.7±13.1 years; 51.8% were aged <45 years; 4% ?65 years. Over 90% of subjects had ?1 of 6 selected modifiable cardiovascular risk factors: 138 (45.6%) had 1-2; 65 (21.5%) had 3; 60 (19.8%) had 4; and 11 (3.6%) had 5 concurrent risk factors. Screening identified 206 subjects (68.0%) with dyslipidemia who did not have a prior diagnosis. Conclusion: Cardiovascular risk factors are highly prevalent in Nigerian subjects attending out-patient clinics. Moreover, many subjects were undiagnosed and therefore unaware of their cardiovascular risk status. Cardiovascular risk factors are highly prevalent in adults attending general out-patient clinics in Nigeria, many of whom were undiagnosed and therefore unaware of their cardiovascular risk status prior to screening. Opportunistic screening alongside intensive national, multisectoral education or risk factor education is needed, should be scaled up nationwide and rolled out in both urban and rural communities in Nigeria.